(untitled) - Hamermesh, Daniel S. (Boston, Mass., 2006)
The purpose of this book is to illustrate the wide range of daily activities to which an economic way of thinking can be applied. A very few of the roughly 400 vignettes are dated to indicate that they were inspired by spmething that came up on that particular day, but most arose from more general musing. They are organized according to the topical arrangement of a typical introductory microeconomics cource. That way they can tie into what you are learning from any standard introductory textbook.
Keywords: Microeconomics,Economics,Kinh tế vi mô,Kinh tế học